Adaptation and Validation of the MapMe Body Image Scales in Spanish Parents of Schoolchildren - Patricia Inclan-Lopez; Maria Martinez-Andres; Angela R. Jones; Martin J. Tovée; Ashley J. Adamson; Raquel Bartolome-Gutierrez (MDPI AG, 2024)
Childhood overweight and obesity is a worldwide problem and to treat it parents' detection has to be improved. The MapMe Body Image Scales (BIS) are a visual tool developed to improve parental perception of child weight in the United Kingdon (UK) based on British growth reference criteria. The aim of this study was to make a transcultural adaptation and validation of the MapMe BIS in Spain based on International Obesity Task Force (IOTF) cut offs A descriptive cross-sectional study was done. First, a translation and cultural adaptation was carried out. A total of 155 10-11-year-old children and their parents participated in this study. Children were measured to calculate their weight status, Body Mass Index (BMI), Body Fat Percentage (BFP) and Waist Circumference (WC), and their parents completed a purpose designed questionnaire about their perception and satisfaction of child's body weight status using the adapted BIS. Test-retest reliability, criterion validity and concurrent validity of the adapted BIS were analyzed. This study shows that the adapted MapMe BIS has good psychometric properties and is a suitable visual scale to assess parental perception of weight status in 10 and 11-year-old children in Spain.